Effect of castor oil based urethane oligomer on properties of UV-curable pressure sensitive adhesive for peelable wafer dicing tape. Issue 23 (1st December 2020) - Hao, Panpan; Sun, Bingyan; Chu, Xiaomeng; Sun, Yujuan; Xing, Xuteng; Liu, Shaojie; Tang, Erjun; Xu, Xiaodong
Abstract: In this work, the isocyanate terminated castor oil based urethane oligomer (CO-IPDI) was prepared by the reaction of castor oil and isophorone diisocyanate (IPDI) without adding any organic solvent. After the acrylic copolymer pressure sensitive adhesive (PSA) was heated at 80 °C for 20 min, it was mixed with CO-IPDI, trifunctional acrylic monomer and photo-initiator in a certain proportion to give a UV-curable peelable adhesive for silicon wafer cutting process. Before UV irradiation, the acrylate copolymer chains were cross-linked by CO-IPDI to form a network. After UV irradiation, another polymer network formed by photo-polymerization of trifunctional acrylic monomer hold together with it to form an interpenetrating network (IPN) structure. The results showed that this IPN structured UV-curable peelable PSA had a high peeling strength of 13.99 N/25 mm before UV curing to meet the suggested requirements for silicon wafer cutting process. The peeling strength was significantly decreased to 0.49 N/25 mm after UV curing, and the tape was easily peeled off from wafer with about 0.96% residual adhesive estimated by the area ratio of all residual adhesive particles to silicon wafer observed by scanning electron microscopy. This work provides a new candidate idea for green and efficient preparation of UV-curable peelable PSA.